Caching algorithm for fast handoff using AP graph with multiple vehicles for VANETs. (1st January 2015) - Das, Debasis; Misra, Rajiv
The vehicular ad–hoc networks (VANETs) encountered frequent handoff due to high mobility of vehicles. The existing schemes are based on the context transfer for fast handoff, but needs to reduce the latency of handoff for VANETs. Fast handoffs in vehicle scans at any instance of time depends upon the association pattern of the AP. In this paper, we have proposed proactive approach for fast handoff using access point (AP) in VANETs. The fast handoff algorithm using AP graph with multiple vehicles for VANETs improves the re–association latency and context transfer procedure must be singled out from re–association process. From the simulation studies, we find that the use of AP graphs reduces the handoff latency due to re–association process and that the effectiveness of the approach improves dramatically as user mobility increases. The protocol for context transfer is defined in inter–access point protocol (IAPP), which infuses proactive transfer technique for frequent handoffs.